Correction: DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew Dewoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)

DNA-based studies and genetic diversity indicator assessments are complementary approaches to conserving evolutionary potential - Sean Hoban; Ivan Paz-Vinas; Robyn E. Shaw; Luis Castillo-Reina; Jessica M. da Silva; J. Andrew DeWoody; Robert Ekblom; Ancuta Fedorca; Brenna R. Forester; W. Chris Funk; Julia C. Geue; Myriam Heuertz; et al. (Conservation Genetics, 2024)
Genetic diversity is essential for maintaining healthy populations and ecosystems. Several approaches have recently been developed to evaluate population genetic trends without necessarily collecting new genetic data. Such “genetic diversity indicators” enable rapid, large-scale evaluation across dozens to thousands of species. Empirical genetic studies, when available, provide detailed information that is important for management, such as estimates of gene flow, inbreeding, genetic erosion and adaptation. In this article, we argue that the development and advancement of genetic diversity indicators is a complementary approach to genetic studies in conservation biology, but not a substitute. Genetic diversity indicators and empirical genetic data can provide different information for conserving genetic diversity. Genetic diversity indicators enable affordable tracking, reporting, prioritization and communication, although, being proxies, do not provide comprehensive evaluation of the genetic status of a species. Conversely, genetic methods offer detailed analysis of the genetic status of a given species or population, although they remain challenging to implement for most species globally, given current capacity and resourcing. We conclude that indicators and genetic studies are both important for genetic conservation actions and recommend they be used in combination for conserving and monitoring genetic diversity.

Conservation genomics of an endangered montane amphibian reveals low population structure, low genomic diversity and selection pressure from disease - D. R. Trumbo; B. M. Hardy; H. J. Crockett; E. Muths; B. R. Forester; R. G. Cheek; S. J. Zimmerman; S. Corey‐Rivas; L. L. Bailey; W. C. Funk (Molecular Ecology, 2023)
Wildlife diseases are a major global threat to biodiversity. Boreal toads ( Anaxyrus [Bufo] boreas ) are a state‐endangered species in the southern Rocky Mountains of Colorado and New Mexico, and a species of concern in Wyoming, largely due to lethal skin infections caused by the amphibian chytrid fungus Batrachochytrium dendrobatidis ( Bd ). We performed conservation and landscape genomic analyses using single nucleotide polymorphisms from double‐digest, restriction site‐associated DNA sequencing in combination with the development of the first boreal toad (and first North American toad) reference genome to investigate population structure, genomic diversity, landscape connectivity and adaptive divergence. Genomic diversity ( π = 0.00034–0.00040) and effective population sizes ( N e = 8.9–38.4) were low, likely due to post‐Pleistocene founder effects and Bd ‐related population crashes over the last three decades. Population structure was also low, likely due to formerly high connectivity among a higher density of geographically proximate populations. Boreal toad gene flow was facilitated by low precipitation, cold minimum temperatures, less tree canopy, low heat load and less urbanization. We found >8X more putatively adaptive loci related to Bd intensity than to all other environmental factors combined, and evidence for genes under selection related to immune response, heart development and regulation and skin function. These data suggest boreal toads in habitats with Bd have experienced stronger selection pressure from disease than from other, broad‐scale environmental variations. These findings can be used by managers to conserve and recover the species through actions including reintroduction and supplementation of populations that have declined due to Bd .

Genetic diversity goals and targets have improved, but remain insufficient for clear implementation of the post-2020 global biodiversity framework - Sean Hoban; Michael W. Bruford; Jessica M. da Silva; W. Chris Funk; Richard Frankham; Michael J. Gill; Catherine E. Grueber; Myriam Heuertz; Margaret E. Hunter; Francine Kershaw; Robert C. Lacy; Caroline Lees; et al. (Conservation Genetics, 2023)
Genetic diversity among and within populations of all species is necessary for people and nature to survive and thrive in a changing world. Over the past three years, commitments for conserving genetic diversity have become more ambitious and specific under the Convention on Biological Diversity’s (CBD) draft post-2020 global biodiversity framework (GBF). This Perspective article comments on how goals and targets of the GBF have evolved, the improvements that are still needed, lessons learned from this process, and connections between goals and targets and the actions and reporting that will be needed to maintain, protect, manage and monitor genetic diversity. It is possible and necessary that the GBF strives to maintain genetic diversity within and among populations of all species, to restore genetic connectivity, and to develop national genetic conservation strategies, and to report on these using proposed, feasible indicators.

A metabolomic signature of the APOE2 allele - Paola Sebastiani; Zeyuan Song; Dylan Ellis; Qu Tian; Michaela Schwaiger-Haber; Ethan Stancliffe; Michael S. Lustgarten; Cory C. Funk; Priyanka Baloni; Cong-Hui Yao; Shakchhi Joshi; Megan M. Marron; et al. (GeroScience, 2023)

Temperature dependence of metabolic rate in tropical and temperate aquatic insects: Support for the Climate Variability Hypothesis in mayflies but not stoneflies - Alisha A. Shah; H. Arthur Woods; Justin C. Havird; Andrea C. Encalada; Alexander S. Flecker; W. Chris Funk; Juan M. Guayasamin; Boris C. Kondratieff; N. LeRoy Poff; Steven A. Thomas; Kelly R. Zamudio; Cameron K. Ghalambor (Global Change Biology, 2021)
A fundamental gap in climate change vulnerability research is an understanding of the relative thermal sensitivity of ectotherms. Aquatic insects are vital to stream ecosystem function and biodiversity but insufficiently studied with respect to their thermal physiology. With global temperatures rising at an unprecedented rate, it is imperative that we know how aquatic insects respond to increasing temperature and whether these responses vary among taxa, latitudes, and elevations. We evaluated the thermal sensitivity of standard metabolic rate in stream‐dwelling baetid mayflies and perlid stoneflies across a ~2,000 m elevation gradient in the temperate Rocky Mountains in Colorado, USA, and the tropical Andes in Napo, Ecuador. We used temperature‐controlled water baths and microrespirometry to estimate changes in oxygen consumption. Tropical mayflies generally exhibited greater thermal sensitivity in metabolism compared to temperate mayflies; tropical mayfly metabolic rates increased more rapidly with temperature and the insects more frequently exhibited behavioral signs of thermal stress. By contrast, temperate and tropical stoneflies did not clearly differ. Varied responses to temperature among baetid mayflies and perlid stoneflies may reflect differences in evolutionary history or ecological roles as herbivores and predators, respectively. Our results show that there is physiological variation across elevations and species and that low‐elevation tropical mayflies may be especially imperiled by climate warming. Given such variation among species, broad generalizations about the vulnerability of tropical ectotherms should be made more cautiously.

Locally adapted traits maintained in the face of high gene flow - S. W. Fitzpatrick; J. C. Gerberich; J. A. Kronenberger; L. M. Angeloni; W. C. Funk (Ecology Letters, 2015)
Gene flow between phenotypically divergent populations can disrupt local adaptation or, alternatively, may stimulate adaptive evolution by increasing genetic variation. We capitalised on historical Trinidadian guppy transplant experiments to test the phenotypic effects of increased gene flow caused by replicated introductions of adaptively divergent guppies, which were translocated from high‐ to low‐predation environments. We sampled two native populations prior to the onset of gene flow, six historic introduction sites, introduction sources and multiple downstream points in each basin. Extensive gene flow from introductions occurred in all streams, yet adaptive phenotypic divergence across a gradient in predation level was maintained. Descendants of guppies from a high‐predation source site showed high phenotypic similarity with native low‐predation guppies in as few as ~12 generations after gene flow, likely through a combination of adaptive evolution and phenotypic plasticity. Our results demonstrate that locally adapted phenotypes can be maintained despite extensive gene flow from divergent populations.

The city‐fox phenomenon: genetic consequences of a recent colonization of urban habitat - P. Wandeler; S. M. Funk; C. R. Largiadèr; S. Gloor; U. Breitenmoser (Molecular Ecology, 2003)
The red fox ( Vulpes vulpes ) is one of the best‐documented examples of a species that has successfully occupied cities and their suburbs during the last century. The city of Zurich (Switzerland) was colonized by red foxes 15 years ago and the number of recorded individuals has increased steadily since then. Here, we assessed the hypothesis that the fox population within the city of Zurich is isolated from adjacent rural fox populations against the alternative hypothesis that urban habitat acts as a constant sink for rural dispersers. We examined 11 microsatellite loci in 128 foxes from two urban areas, separated by the main river crossing the city, and three adjacent rural areas from the region of Zurich. Mean observed heterozygosity across individuals and the number of detected alleles were lower for foxes collected within the city as compared with their rural conspecifics. Genetic differentiation was significantly lower between rural than between rural and urban populations, and highest value of pairwise F ST was recorded between the two urban areas. Our results indicate that the two urban areas were independently founded by a small number of individuals from adjacent rural areas resulting in genetic drift and genetic differentiation between rural and urban fox populations. Population admixture and immigration analysis revealed that urban–rural gene flow was higher than expected from F ST statistics. In the five to seven generations since colonization, fox density has dramatically increased. Currently observed levels of migration between urban and rural populations will probably erode genetic differentiation over time.